School Strategy in Preventing Bullying Behavior at SMAN 1 Lambu - Riswan Anas; Syafruddin; Wahyu Mulyadin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims at school strategies in handling and preventing bullying behavior that occurs in the SMAN 1 Lambu environment and the factors that cause bullying cases that occur in the school environment. The research method used is descriptive qualitative, with data sources taken from teachers and students as well as journals, books and theses. Data collection techniques using observation, interviews and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. To test the credibility of the data by member checking, cross checking and triangulation. The results of this research are that the school's strategy to prevent bullying behavior that occurs at SMAN 1 Lambu is to do several things, namely forming an anti-bullying team, providing numbers and complaint boxes, an imtak program, monitoring on social media and education and warning students about the dangers of bullying. Factors that cause bullying cases to occur in the SMAN 1 Lambu environment are still frequently encountered, while some influence them so that children tend to carry out bullying acts. Factors that often occur at SMAN 1 Lambu are individual personality, family, school, peer group, social environment and community, adverse children's experience (bad childhood experiences).